In System T its possible to conclude:

(1) □Ex->Ex

Therefore its possible to conclude:

(2) Ex->◊Ex

But whats the result, if I negate the existence quantifier? Is it:

(3) ~Ex->~◊Ex

or is it:

(4) ~Ex->◊~Ex

I found nothing in the usual introduction textbooks, but Im not a (modal) logic expert. Im thankful for all your answers

  • Not clear; you are trying to derive the negated formula from what ? – Mauro ALLEGRANZA Jan 7 '18 at 13:43
  • You have to negate formulas, and not quantifiers. – Mauro ALLEGRANZA Jan 7 '18 at 13:44
  • My question is: If nothing existists (~Ex), is it inpossible (~◊) that something existists (Ex)? That is what I was going for with (3). And can i show (3) in the T system? – Mr_Lampe Jan 7 '18 at 13:49
  • 1
    Obviously, (4) follows from (2). – Mauro ALLEGRANZA Jan 7 '18 at 13:56
  • From (1), by contrapostion, we get: ~∃x → ~□∃x i.e. ~∃x → ◊~∃x. – Mauro ALLEGRANZA Jan 7 '18 at 13:58

As @MauroALLEGRANZA mentions, you do get

(4) ~Ex->◊~Ex

I'd say it just follows from System T in general:

System T makes the accessibility relation reflexive, so that if there is no x with a certain property P in a world w, then there is a possible world relative to w, namely w itself, where there is no x with property P.

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.